2012
DOI: 10.1021/la303568e
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Block Copolymer–Nanoparticle Hybrids: Interplay between Enthalpy and Entropy

Abstract: The dispersion of nanoparticles in ordered block copolymer nanostructures can provide control over particle location and orientation, and pave the way for engineered nanomaterials that have enhanced mechanical, electrical, or optical properties. Fundamental questions pertaining to the role of enthalpic and entropic particle-polymer interactions remain open and motivate the present work. We consider here a system of 10.6 nm silica nanoparticles (NPs) dispersed in ordered cylinders formed by hydrated poly(ethyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 80 publications
0
57
0
Order By: Relevance
“…Several studies have shown that NP incorporation into a specific location of ordered BCPs caused order-to-order phase transitions [67,78,118,119,120,121]. In addition to inducing structural transitions, NP incorporation can also influence the characteristic size of the nanodomains [75,122]. Below we discuss the effect of NPs on the overall phase behavior / morphology and on the characteristic length-scales of BCP nanostructures.…”
Section: Page 13 Of 96mentioning
confidence: 98%
See 3 more Smart Citations
“…Several studies have shown that NP incorporation into a specific location of ordered BCPs caused order-to-order phase transitions [67,78,118,119,120,121]. In addition to inducing structural transitions, NP incorporation can also influence the characteristic size of the nanodomains [75,122]. Below we discuss the effect of NPs on the overall phase behavior / morphology and on the characteristic length-scales of BCP nanostructures.…”
Section: Page 13 Of 96mentioning
confidence: 98%
“…A c c e p t e d M a n u s c r i p t 9 The location of NPs and the overall BCP-NP morphology are dictated by properties of the NPs (such as size, concentration, and surface chemistry), properties of the block copolymers (such as chemistry, conformation, and molecular weight), and the presence of small molecules [73][74][75].…”
Section: Mechanism Of Nanoparticle Incorporationmentioning
confidence: 99%
See 2 more Smart Citations
“…An efficient method of controlling the enthalpy interactions is the modification of the nanoparticle surface by grafting of organic ligands. These should be chemically compatible with one of the blocks of the block copolymer [25][26][27][28][29]. Quite recently we have reported the influence of PEG POSS Ò (poly (ethylene glycol) functionalized POSS) incorporation in two grades of the commercial poly(ether-block-amide) thermoplastic elastomer PEBAX Ò upon CO 2 separation performance [30,31].…”
Section: Introductionmentioning
confidence: 99%